Kek-6: A truncated-Trk-like receptor for Drosophila neurotrophin 2 regulates structural synaptic plasticity. - Ulian-Benitez, S.; Bishop, S.; Foldi, I.; Wentzell, J.; Okenwa, C.; Forero, M.G.; Zhu, B.; Moreira, M.; Phizacklea, M.; McIlroy, G.; Li, G.; Gay, N.J.; et al. (PLoS Genetics, 2017)
Neurotrophism, structural plasticity, learning and long-term memory in mammals critically depend on neurotrophins binding Trk receptors to activate tyrosine kinase (TyrK) signaling, but Drosophila lacks full-length Trks, raising the question of how these processes occur in the fly. Paradoxically, truncated Trk isoforms lacking the TyrK predominate in the adult human brain, but whether they have neuronal functions independently of full-length Trks is unknown. Drosophila has TyrK-less Trk-family receptors, encoded by the kekkon (kek) genes, suggesting that evolutionarily conserved functions for this receptor class may exist. Here, we asked whether Keks function together with Drosophila neurotrophins (DNTs) at the larval glutamatergic neuromuscular junction (NMJ). We tested the eleven LRR and Ig-containing (LIG) proteins encoded in the Drosophila genome for expression in the central nervous system (CNS) and potential interaction with DNTs. Kek-6 is expressed in the CNS, interacts genetically with DNTs and can bind DNT2 in signaling assays and co-immunoprecipitations. Ligand binding is promiscuous, as Kek-6 can also bind DNT1, and Kek-2 and Kek-5 can also bind DNT2. In vivo, Kek-6 is found presynaptically in motoneurons, and DNT2 is produced by the muscle to function as a retrograde factor at the NMJ. Kek-6 and DNT2 regulate NMJ growth and synaptic structure. Evidence indicates that Kek-6 does not antagonise the alternative DNT2 receptor Toll-6. Instead, Kek-6 and Toll-6 interact physically, and together regulate structural synaptic plasticity and homeostasis. Using pull-down assays, we identified and validated CaMKII and VAP33A as intracellular partners of Kek-6, and show that they regulate NMJ growth and active zone formation downstream of DNT2 and Kek-6. The synaptic functions of Kek-6 could be evolutionarily conserved. This raises the intriguing possibility that a novel mechanism of structural synaptic plasticity involving truncated Trk-family receptors independently of TyrK signaling may also operate in the human brain.